PENERAPAN LABORATORY INSTRUCTION DALAM PROSES PEMBELAJARAN MATA KULIAH GIZI OLAHRAGA - JUMHAN PIDA (Jurnal Kependidikan, 2004)
Abstract The purpose of this research is to develop sport nutrients subject absorbent to the students of Sport Coach Education (SCE) Sport Science Faculty (SSF) at Yogyakarta State University. The raising of comprehended hoping measured by getting point from this subject itself, than totally it will improve the average of GPA (Grade Point Average). Research Design is classroom action through some cycle of activities: planning, acting, observing, and reflecting. Research Subject is Study Program of SCE of SSF Yogyakarta State University students in fifth grade who take sport nutrients subject about 51 students. For monitoring and noting in class is done through observation by two observers using observation sheet. The action of evaluating and reflecting is done through analyzing the result of observation. To evaluate the research result is by comparing between the points for this subject before using laboratory instruction method (period 2001, 2002, and 2003) and after using this method period 2004. The research result shows that laboratory instruction can raise the comprehended of sport nutrients subject to the students of SCE in Yogyakarta State University. The rise of comprehension consists of: point A increases 5.8%, point A- increases 8.2%, point B+ increases 1.9 %, point B increases 30%, point B- increases 4.8%, point C+ increases 2.8 %, point C decrease 43.3%, point D decrease 6.1%. Evaluating by PAP (Penilaian Acuan Patokan) System. Keywords: laboratory instruction, sport nutrition